Differential effects of hexaconazole and paclobutrazol on the foliage characteristics of Chinese potato (Solenostemon rotundifolius Poir., J.K. Morton) - Kishorekumar, Ashok (Acta Biologica Szegediensis, 2006)
In the present investigation, the impact of hexaconazole (HEX) and paclobutrazol (PBZ), triazole fungicides, on the leaf anatomy of Chinese potato (Solenostemon rotundifolius Poir., J.K. Morton) was studied. The thickness of leaf, upper and lower epidermis, number of palisade and spongy cells per unit area, number of chloroplast per palisade and spongy cells, number of stomata in upper and lower epidermis, stomatal pore length and width were observed in both control and treatments. Leaves treated with HEX and PBZ showed several variations in the anatomical characteristics.